Prognosis for intracerebral hemorrhage during ongoing oral anticoagulant treatment. (14th February 2019) - Apostolaki‐Hansson, Trine; Ullberg, Teresa; Norrving, Bo; Petersson, Jesper
Abstract: Background: Intracerebral hemorrhage (ICH) is the most serious adverse effect of treatment with oral anticoagulants. Prognostic data after ICH associated with non‐vitamin K antagonist oral anticoagulants (NOAC) compared to vitamin K antagonists (VKA) are sparse. We compared 90‐day survival and functional outcome following NOAC‐ICH versus VKA‐ICH using data from the Swedish Stroke Register (Riksstroke). Methods: Using data from Riksstroke and the Swedish Causes of Death Register between 2012 and 2016, we compared all‐cause 90‐day mortality for patients with NOAC‐ICH versus VKA‐ICH using Kaplan‐Meier survival analysis and Log‐rank test. Cox regression, with adjustment for age, sex, previous stroke, and level of consciousness (LOC) on admission, was used to estimate hazard ratios (HR) for 90‐day mortality. Estimated functional outcome at 90 days, based on the modified Rankin Scale (mRS), was compared between VKA‐ and NOAC‐associated ICH using chi‐squared test. Results: We included 2483 patients; 300 with NOAC‐ICH and 2183 with VKA‐ICH. In both groups, mean age was 79 years, and 58% were male. No significant difference between NOAC‐ICH and VKA‐ICH was found for all‐cause 90‐day mortality (44.3% NOAC‐ICH versus 42.6% VKA‐ICH; P = 0.54, HR = 0.93; 95% confidence interval (CI): 0.78‐1.12) or 90‐day estimated functional outcome (mRS 0‐2:13.7% and 15.3%; mRS 3‐5:27.3% and 28.9%, respectively ( P = 0.52)). Factors predicting death were increased age (HR = 1.03; 95%CI: 1.02‐1.04) and reduced LOC (drowsy: HR = 3.48; 95%CI: 2.86‐4.23; comatose: HR = 12.27; 95%CI: 10.13‐14.87). Conclusion: In this large study on anticoagulant‐associated ICH, we found no significant difference in mortality and functional outcome at 90 days between NOAC‐ICH versus VKA‐ICH.